PENGARUH KOMUNIKASI INTERPERSONAL, KUALITAS PELAYANAN CUSTOMER SERVICE DAN CITRA MEREK TERHADAP KEPUASAN NASABAH PADA PENGGUNA APLIKASI BRImo (Ekonomika, 2021)
The quality of the company plays an active role in increasing customer satisfaction through variables that influence it, including interpersonal communication, customer service quality, and brand image. The problem formulation of this research is whether interpersonal communication, customer service quality, and brand image have a significant effect on customer satisfaction. This research method is descriptive quantitative. The research was conducted by searching for primary data through questionnaires to customers which was carried out using probability sampling method so that 100 samples were obtained from 133 populations. The research data was processed by statistical analysis with Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination, and Hypothesis Testing (t-test and f-test). The aims of this study are to determine the effect of: interpersonal communication, customer service quality and brand image on customer satisfaction. The results of the study are: 1) interpersonal communication has a significant effect on customer satisfaction. 2) the quality of customer service has a significant effect on customer satisfaction. 3) brand image has a significant effect on customer satisfaction. 4) interpersonal communication, customer service quality, and brand image together have a significant effect on customer satisfaction. Suggestions for further researchers to conduct further research discussing a wider scope such as adding other variables.